Relapse-free cure from multidrug-resistant tuberculosis in Germany - Heyckendorf, Jan Sebastian; Leth, Frank van; Kalsdorf, Barbara; Olaru, Ioana D.; Günther, Gunar; Salzer, Helmut J. F.; Terhalle, Elena; Rolling, Thierry; Glattki, Georg; Müller, Marius; Schuhmann, Maren; Avsar, Korkut; et al. (The European respiratory journal, 2018)
Tweetable abstract ERSpublications - click to tweetUnder optimal conditions we observed similar rates of relapse-free cure in patients with M/XDR-TB and non-M/XDR-TB http://ow.ly/SRvd30hPu73